ANALISIS KEBUTUHAN PENGEMBANGAN PEMBELAJARAN BERDIFERENSIASI KONTEN BERBASIS QR CODE PADA MATA PELAJARAN PPKN DI MAN KOTA TEGAL - Hardini Sudibyo, Ismi; Kusrina, Tity; Suriswo, Suriswo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the needs of students and teachers regarding the development of QR Code-based content-differentiated learning methods in Civic Education (PPKn) at MAN Kota Tegal. The primary challenges in teaching PPKn include the tendency for material to be perceived as abstract and the diverse characteristics of students within the classroom. This study represents the preliminary stage of a Research and Development (R&D) project. The research method employed is descriptive qualitative, with data collection techniques involving semi-structured interviews with PPKn teachers, classroom observations, and the distribution of needs assessment questionnaires to 64 eleventh-grade students across two classes. The results reveal three main findings: (1) There is a diversity of student learning styles (visual, auditory, kinesthetic) that have not been optimally facilitated by current teaching methods, which remain dominated by lectures; (2) Students face difficulties in understanding conceptual and procedural PPKn material, yet they demonstrate a high interest in using mobile devices for learning; (3) Teachers require practical tools to implement content differentiation without significantly increasing their administrative burden. Furthermore, the availability of smartphones and internet access within the school environment is highly supportive. It is concluded that the development of QR Code-based content-differentiated learning methods is urgent and highly relevant for implementation at MAN Kota Tegal to bridge the gap in student learning needs.